DIGITAL MARKETING COMMUNICATION STRATEGIES IN THE ERA OF DISRUPTION - Romano Aulia Rahman (Jurnal Kebijakan Publik, 2024)
The era of technological disruption has fundamentally changed the way companies run business and interact with customers. This research aims to explore effective digital marketing communication strategies amidst this rapid change. The research method used is a qualitative approach with case studies of several companies that have successfully implemented digital marketing strategies. Data was collected through in-depth interviews, content analysis, and digital activity observations. The research results identified several key elements of a successful strategy, including leveraging data and analytics to understand consumer behavior, personalizing relevant content through AI and machine learning technology, marketing automation for operational efficiency, and optimizing the customer experience across various digital touchpoints. Apart from that, the use of social media for engagement and collaboration with influencers to increase brand visibility has also proven to be effective. The conclusions of this research emphasize the importance of a data-based, personalized, automated and customer-centric approach in digital marketing communications strategies.